The Influence of Intellectual Capital and Financial Performance on the Stock Prices of Commercial Banks in Indonesia with Company Size as a Moderation Variable - Sigalingging, Ezra Ezran (Devotion : Journal of Research and Community Service, 2024)
This study aims to test and analyse the effect of intellectual capital consisting of Value Added Intellectual Capital (VAICTM) and financial performance proxied by Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Return On Asset (ROA) on stock prices with company size as a moderating variable. The research data is secondary data with a 6-year observation period. The population in this research is banks classified as KBMI III and IV banks. The sampling method used is non-probability sampling, with the consideration that banks with KBMI III and IV categories are top-tier banks whose performance has a systemic impact. The data sample taken is 13 banks, in accordance with OJK-RI provisions. Data collection techniques through documentation using panel data regression analysis, namely Eviews13. The results of this study (VAICTM) and CAR have no effect on stock prices. ROA and NPL have a significant effect on stock prices. Company size moderates the (VAICTM) and ROA variables while NPL and CAR can’t be moderated by company size.